2004
DOI: 10.1038/sj.bjc.6602219
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hypoxia in an experimental rat tumour model by [18F]Fluoromisonidazole PET and immunohistochemistry

Abstract: This study aimed to evaluate tumour hypoxia by comparing [ 18 F]Fluoromisonidazole uptake measured using positron emission tomography ([ 18 F]FMISO-PET) with immunohistochemical (IHC) staining techniques. Syngeneic rhabdomyosarcoma (R1) tumour pieces were transplanted subcutaneously in the flanks of WAG/Rij rats. Tumours were analysed at volumes between 0.9 and 7.3 cm 3 . Hypoxic volumes were defined using a 3D region of interest on 2 h postinjection [ 18 F]FMISO-PET images, applying different thresholds (1.2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(56 citation statements)
references
References 43 publications
3
48
0
1
Order By: Relevance
“…Simultaneously with tracer injection (20.430 ± 2.418 MBq), a dynamic emission scan in list mode (LM) was started for 60 min in one bed position encompassing the heart, tumor, and hind legs of the rat. Afterward, LM data were rebinned using Fourier rebinning, and PET images were reconstructed as previously described (5). Two hours post injection, the rats were repositioned using external markers and a dedicated laser-positioning system (LAP) for a CT scan, immediately followed by a second dynamic emission scan performed for 20 min (rebinned into four frames of 5 min each).…”
Section: Resultsmentioning
confidence: 99%
“…Simultaneously with tracer injection (20.430 ± 2.418 MBq), a dynamic emission scan in list mode (LM) was started for 60 min in one bed position encompassing the heart, tumor, and hind legs of the rat. Afterward, LM data were rebinned using Fourier rebinning, and PET images were reconstructed as previously described (5). Two hours post injection, the rats were repositioned using external markers and a dedicated laser-positioning system (LAP) for a CT scan, immediately followed by a second dynamic emission scan performed for 20 min (rebinned into four frames of 5 min each).…”
Section: Resultsmentioning
confidence: 99%
“…[41][42][43][44][45][46][47][48] Early reports suggested that semiquantitative scoring of CAIX labeling was correlated with direct pO 2 measurements in solid tumors, but this has not been confirmed by other groups. [32][33][34][35][36][49][50][51][52][53] When we examined a series of single punch biopsies obtained from Figure 5 The 95% CI of the averaged per patient % carbonic anhydrase IX (CAIX) value, in full sections (a) and in tissue microarray (TMA) simulations (b and c).…”
Section: Discussionmentioning
confidence: 99%
“…Most solid tumors show evidence of hypoxia, presumably as a consequence of tumor cell proliferation outpacing neoangiogenesis (1)(2)(3). To date, three methods have been used to assess hypoxia in human tumors.…”
Section: Introductionmentioning
confidence: 99%